Microbial Quality Analysis of Panipuri Samples Collected from Different Parts of Bhaktapur (Tribhuvan University Journal of Microbiology, 2021)
Objectives: The study was aimed to identify potential bacterial pathogens from the panipuri samples collected from different vendors of Bhaktapur district and determine their antibiogram patterns.Methods: Altogether 120 (40 puri, 40 stuffing and 40 pani) samples of panipuri were collected from different vendors of Bhaktapur district in a cold chain and were transported to the microbiology laboratory. Puri and stuffing were then pre-enriched, enriched and cultured while pani samples were processed using the MPN method. All the isolates were identified following standard microbiological procedure and subjected to antibiotic susceptibility testing following CLSI guidelines.Results: The result revealed contamination of 77.5% stuffing, 67.5% puri and 52.5% pani samples with pathogenic bacteria. Among bacterial pathogens, the highest number was Staphylococcus aureus followed by Escherichia coli and Salmonella spp. 100% of S. aureus were found to be resistant to ampicillin and novobiocin. Similarly, 94.1% of E. coli were resistant to ampicillin followed by ciprofloxacin (64.7%). A very few isolates of Salmonella spp, Shigella spp and Vibrio spp were resistant to tetracycline. The highest number of multidrug-resistant bacteria were S. aureus, followed by Klebsiella spp and E. coli. Conclusion: The study showed that the panipuri samples from street vendors were found to be highly contaminated with pathogenic bacteria which might affect consumers’ health. Thus, to prevent any food-borne illness in the future, frequent evaluation and regulation of the quality of such foods should be carried out.